The biochemistry behind human behavior: Implications for leisure sciences and services. (2nd November 2019) - Dustin, Daniel L.; Zajchowski, Chris A. B.; Schwab, Keri A.
Abstract: This research reflection explores the relationship between biochemistry and human behavior. More specifically, it examines the implications associated with two neural pathways in the brain, one leading to pleasure and the other to contentment. After describing how the two pathways work and where they lead, we turn the reader's attention to the implications for leisure sciences and services, including the way we think about leisure behavior, how we plan for it, and, ultimately, how we might rethink the leisure service profession's obligation in light of its classical philosophical foundations.